Tingkat Ekonomi dan Partisipasi Etnis Tionghoa dalam Pilkada Kota Medan - BOBBY IRWANSYAH (Universitas Sumatera Utara, 2010)
The election of regional leader directly or recognized with the term “Pilkadasung” has been conducted at Medan City, June 2005. At this moment, political participation of society has shared at certain level. This article explores relation of level economic with political participa-tion ethnic Tionghoa society at Pilkadasung 2005 Medan City based on Lingkungan VI Kelura-han Pusat Pasar Medan Kecamatan Medan Kota. As the same manner as known, Tionghoa is one of the ethnical exist in Indonesia which majority having living in private sector and they have wide access for ownership of economics resources. And so do in Medan City. This study finding, it’s exactly have implications to political participation. Their involvement in politics is high and significance. Its clear statement, that getting higher economy level then getting higher political participation. But, the Tionghoa ethnic political participation in secure manner, such as participating in the material. Participation is motivated by the hope of future business flu-ency.Keywords: Political participation, Political behaviour, Ethnical behaviour.